Primary large cell neuroendocrine carcinoma of the urethra: a case report - Jianbai Chen; Xiaorong Mou; Zhiming Zhang; Zhiyong Nie; Jianxin Qiu (Frontiers in Urology)
BackgroundPrimary neuroendocrine carcinoma of the urethra is a very uncommon malignant tumor, and no reports have been made about large cell neuroendocrine carcinoma (LCNEC) in the past.Case descriptionA 43-year-old non-smoking female patient presented with symptoms of dysuria and urination-related pain at TangDu Hospital in April 2022. A biopsy subsequently confirmed the diagnosis of primary urethral LCNEC. Following radical resection, the patient exhibited abnormal lymph node enlargement in the first month and pelvic metastases in the fourth month. Ultimately, the patient succumbed to the disease 486 days after the radical resection, attributed to widespread tumor metastases and concurrent multi-organ failure. The final pathological examination confirmed the presence of a high-grade LCNEC.ConclusionThe occurrence of primary LCNEC in the urethra is exceptionally uncommon. This particular instance was notable for its aggressive progression and unfavorable prognosis. Historically, there have been no prior documented instances of primary pure LCNEC in the urethra. It is imperative to emphasize that early identification and intervention for LCNEC could potentially offer patients a more favorable survival outcome.